Evaluasi implementasi aplikasi digital aum seri-umum berbasis website: persepsi konselor sekolah terhadap inovasi aum - Ifdil Ifdil; Rima Pratiwi Fadli; Nellitawati Nellitawati; Zadrian Ardi; Eval Edmizal; Jeky Haryanto; Annisaislami Khairati; Nur Adila Wafiqah Zulvi (Jurnal Konseling dan Pendidikan, 2025)
This study evaluates the implementation of the digital AUM Seri-Umum application based on school counselors’ perceptions after attending a structured workshop. A cross-sectional survey was conducted with 37 guidance and counseling teachers who participated in the training. Data were collected using a Likert-scale questionnaire covering clarity of materials, ease of use, workshop convenience, perceived usefulness, satisfaction, and intention to use, complemented by open-ended responses. Descriptive statistics and thematic coding were employed in the analysis. Findings show that the application was very well received, with a composite mean score of 4.93, indicating highly positive perceptions. Counselors highlighted the clarity of instructions, user-friendly navigation, and strong practical benefits in managing student problems efficiently. Notably, 100% of participants expressed satisfaction and intention to continue using the application, with enthusiasm to join future workshops. These results confirm that the digitalization of AUM Seri-Umum is a strategic innovation supporting more effective, efficient, and data-driven counseling services in schools